PD‐L1 in squamous cell carcinoma of the oral tongue shows gender‐specific association with prognosis. (6th July 2020) - Wilms, Torben; Gu, Xiaolian; Boldrup, Linda; Coates, Philip J.; Fahraeus, Robin; Wang, Lixiao; Sgaramella, Nicola; Nielsen, Niels‐Hilmer; Norberg‐Spaak, Lena; Nylander, Karin
Abstract: Objective: To use alternative quantitation approaches to clarify the clinical implication of programmed cell death ligand 1 (PD‐L1) in squamous cell carcinoma of the oral tongue (SCCOT). Materials and Methods: Ventana SP263 immunohistochemistry assay and a multiplicative QuickScore method were applied to quantify PD‐L1 in tumor and surrounding immune cells from 101 patients with SCCOT. Tumor‐infiltrating immune cells were estimated from bulk tissue transcriptional profiles of 25 patients. Circulating PD‐L1 levels were measured in serum from 30 patients using an electrochemiluminescence assay platform. Results: We found higher tumor cell PD‐L1 levels in females than males ( p = .019). For patients with low PD‐L1 in tumor cells, better survival was seen in males than females (overall survival p = .021, disease‐free survival p = .020). Tumor‐infiltrating natural killer T cells, immature dendritic cells, and M1 macrophages were positively associated with tumor cell PD‐L1 ( p < .05). Conclusions: Our data confirmed the significance of gender on tumor cell PD‐L1 expression and demonstrated combined effects of gender and PD‐L1 levels on clinical outcome in patients with SCCOT. The data also indicated the involvement of specific immune cell types in PD‐L1‐regulated immune evasion.